Quantifying yield losses due to barley yellow dwarf on winter wheat in Kansas using disease phenotypic data - Gaunce, Genna Marie (Kansas State University, 2014)
Barley yellow dwarf (BYD) is one of the most important wheat diseases in the state of Kansas. Despite the development of cultivars with improved levels of resistance to BYD, little is known about the impact that this resistance has on yield loss from the disease. The intent of this research was to estimate yield loss in winter wheat cultivars in Kansas due to BYD and quantify the reduction in losses associated with resistant cultivars. During seven years, BYD disease incidence was visually assessed on numerous winter wheat cultivars in replicated field nurseries. Cultivars were planted about three weeks early to promote disease. When grain yields were regressed against BYD incidence scores, negative linear relationships significantly fit the data for each year and for the combined dataset covering all seven years. The models showed that, depending upon the year, 19-48% (average 33%) of the yields was explained by BYD incidence. For the combined dataset, 29% of the relative yield was explained by BYD incidence. The models predicted that cultivars showing high disease incidence had 25-86% (average 49%) less yield than a hypothetical cultivar that showed zero incidence. Using the models, the moderate level of resistance in the cultivar Everest was calculated to reduce yield loss from BYD by about 73%. Therefore, utilizing visual BYD symptom evaluations in Kansas, coupled with grain yields, is useful to estimate yield loss from the disease. Furthermore, linear models that incorporate those parameters can be used to calculate the impact of improving cultivar resistance to BYD on yield losses.
Keywords: Virus; Phenotype; Barley yellow dwarf; Wheat; Linear regression; Hard red winter wheat; Agriculture, General (0473); Plant Pathology (0480); Plant Sciences (0479)